A multiscale wear simulation method for rotary lip seal under mixed lubricating conditions. (May 2018) - Liu, Di; Wang, Shaoping; Zhang, Chao
Abstract: The macroscale simulation methods are commonly used to study wear of rotary lip seals. These methods oftentimes do not address effects of microscopic interfaces, which, according to experimental studies, are important factors in the wear of rotary lip seal. Hence, a multiscale wear simulation method for rotary lip seal under mixed lubricating conditions is proposed, in which the effects of microscopic aspects of interacting surfaces are taken into account. The simulation results indicate that the wear of rotary lip seal can be reduced by reducing axial asperity density while increasing the circumferential asperity density. The results also indicate that wear of the rotary lip seal is susceptible to axial asperity density when it is within a particular range. Highlights: A multiscale wear simulation method for rotary lip seal in mixed lubricated condition is proposed. The influence of lubrication characteristics of sealing zone on the wear of rotary lip seal is taken into consideration. This method can be used to analyze the influence of microscopic aspects on the wear of rotary lip seal. The effect of shaft surface on seal wear is studied to find which kind of shaft surface is more helpful to retard seal wear. The wear time rate increases with increase of axial asperity density and decrease of circumferential asperity density.